Vietnamese EFL Teachers' and Students' Perceptions of Using Translanguaging in Language-Integrated Literature Courses: A Qualitative Study - Tuyet Nhung Thi Nguyen (IGI Global, 2024)
This chapter reports a case study on Vietnamese EFL student and teacher perceptions of the benefits and difficulties of using translanguaging in literature courses. Using semi-structured interviews and thematic analysis, this study engaged seven students and five teachers to address the research questions. The results revealed that the students perceived benefits in using Vietnamese in teaching English literature courses, including improving understanding and analyses of literary works, cultural connections, and group interactions. Similarly, the teachers recognized benefits such as increasing comprehension, student engagement, cultural awareness, and confidence. However, students encountered difficulties related to the use of colloquial language, translation complexities, and cultural disparities. Likely, teachers observed diminishing student engagement, hindrances to students' English language proficiency, and comprehension difficulties. These results thereby contribute to the existing understanding of translanguaging in the classroom.